CinemaAfrica 2025/26: A Conversation with ... Stewart Sukuma (Cinema Africa 2025/26, 2026)
In this video, legendary Mozambican musician Stewart Sukuma sits down for an in-depth conversation with Prof. Dr. Ute Fendler, curator of the Cinema Africa film festival in Bayreuth, Germany. Their discussion, recorded on 23 January 2026, explores Sukuma’s artistic journey, the intersections of music and film, and his role in the festival’s program. Sukuma was part of the festival’s opening night celebration for “The Anchorage of Time” (Ancoradouro do Tempo), a Mozambican/Portuguese crime drama screened at the 17th Cinema Africa film festival held at Cineplex Bayreuth a few days later. The conversation offers rare personal insights into Sukuma’s creative process and his reflections on African cinema, culture, and global artistic exchange. For anyone interested a link to Stewart Sukuma's book is: https://www.poesiaimpossivel.com/o-alfaiate-e-a-arte-de-costurar-o-amor